Branched polymer for selective water control of oil well and preparation method thereof
By performing aldehyde and amino modification of nanocellulose and preparing branched polymers by radical polymerization, the problems of molecular curling and degradation of existing selective water-controlled polymers under high temperature and high salts are solved, and excellent water-controlled effect and long-term stability under strong injection and production conditions are achieved.
Patent Information
- Application Number
- CN202411947661.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-14
AI Technical Summary
The existing selective water-control polymers are molecularly curled and degraded in high-temperature and high-salt reservoirs, resulting in a decrease in oil-water selection capacity. The retention capacity of water-control agents is poor under strong injection and production conditions, and the water-control effect continues to decline.
The nanocellulose is oxidized by an oxidizing agent to prepare aldehyde-based nanocellulose, and its dispersion and reactivity are improved through amino modification. Then, the redox reaction of aminolated nanocellulose and Ce4+ generates free radicals as the starting reaction site for the preparation of branched polymers, and polymers with branched structures are prepared by aqueous solution polymerization.
This branched polymer has excellent water control effect under long-term erosion, improving long-term stability under high temperature and high salt and retention ability in porous media.
Smart Images

Figure BDA0005214086360000051 
Figure BDA0005214086360000061 
Figure BDA0005214086360000062
Abstract
Description
Technical Field
[0001] The invention relates to a branched polymer used for selective water control of oil wells and a preparation method thereof, belonging to the technical field of oilfield chemistry. Background Art
[0002] As oilfield exploitation proceeds, the amount of water produced by the oil layer gradually increases, resulting in a decrease in oil production, reduced oil well pump efficiency, and an increase in the burden of sewage treatment. Selective water control agents, as chemicals to solve such problems, can significantly reduce the permeability of water while having little effect on the permeability of oil, and have achieved good water control and oil stabilization effects in field applications. However, conventional selective water control polymers based on acrylamide polymers still have shortcomings in their applications. For example, in high-temperature and high-salinity reservoirs, they will undergo molecular curling and degradation, resulting in a decrease in oil-water selectivity; in addition, since the middle and late stages of oilfield development mainly adopt a strong injection and strong production development method, the retention capacity of water control agents is poor under the continuous flushing of a large amount of liquid, and the water control effect continues to decline. Therefore, it is urgent to improve the long-term stability of selective water control polymers under high temperature and high salt, as well as their retention capacity in porous media under long-term flushing.
[0003] Nanocellulose is a linear biomass nanomaterial with a large specific surface area, and has good water phase dispersion, high temperature stability, mechanical strength and environmental protection properties. The abundant hydroxyl groups on the surface of nanocellulose can interact with polymers or other small molecules, and other functional groups can also be introduced through surface modification. Therefore, with nanocellulose as the core, free radical polymerization can be used to graft olefin monomers onto its surface to prepare a branched polymer structure. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides a branched polymer for selective water control in oil wells and a preparation method thereof. SUMMARY OF THE INVENTION
[0006] The present invention first oxidizes nanocellulose with an oxidant to prepare aldehyde-modified nanocellulose, then uses the aldehyde group to react with a polyamine compound to undergo a Schiff base reaction to further modify the nanocellulose with an amination reaction, and then uses a reducing agent to reduce the obtained amination-modified nanocellulose to improve its dispersibility and reactivity. 4+ The redox reaction between the two generates free radicals on the amino nanocellulose molecules, which serve as the starting reaction sites for preparing branched polymers. Nonionic water-soluble monomers, anionic water-soluble monomers, hydrophobic monomers, etc. are used as raw materials to prepare polymers with branched structures through aqueous solution polymerization. Tests have shown that the branched polymer has excellent water control effect under long-term flushing. DETAILED DESCRIPTION OF THE INVENTION
[0008] The technical solution of the present invention is as follows.
[0009] A branched polymer for selective water control in oil wells and a preparation method thereof, comprising the following steps:
[0010] (1) Preparation of aldehyde-modified nanocellulose
[0011] Add nanocellulose to deionized water, perform ultrasonic dispersion, add oxidant, control pH to 5-8, control temperature to 30-60°C, react for 2-6 hours in dark, filter, wash and dry the product to obtain nanocellulose; the diameter of nanocellulose is 4-10 nm, the length is 20-200 nm, and the mass ratio of nanocellulose, oxidant and deionized water is 1:(0.1-3):(30-100);
[0012] (2) Preparation of amino-modified nanocellulose
[0013] The aldehyded nanocellulose is added to deionized water, ultrasonically dispersed, a polyamine compound is added, the pH is controlled at 5-7, the temperature is controlled at 20-35°C, the reaction is carried out for 4-8 hours, and after the reaction is completed, a reducing agent is added, the temperature is controlled at 20-30°C, the reaction is carried out for 3-5 hours, and the product is filtered and dried to obtain the product; the mass ratio of the aldehyded nanocellulose, the polyamine compound, the reducing agent, and the deionized water is 1: (0.5-5): (0.1-2): (50-200);
[0014] (3) Preparation of branched polymers
[0015] Add nonionic water-soluble monomer, anionic water-soluble monomer, hydrophobic monomer, amino nanocellulose, surfactant and deionized water into a three-necked glass bottle equipped with a stirrer, a nitrogen tube and a thermometer, stir until all the raw materials are dissolved, introduce nitrogen for 30 minutes, control the pH to 5-8, and the temperature to 0-10°C, add a complexing agent and a cerium-containing compound, react for 3-6 hours, dry and grind the product to obtain; the mass ratio of nonionic water-soluble monomer, anionic water-soluble monomer, hydrophobic monomer and amino nanocellulose is 1:(0.2-2):(0.01 ~0.2):(0.01~0.1), the ratio of the total mass of nonionic water-soluble monomers, anionic water-soluble monomers, hydrophobic monomers, and amino nanocellulose to the mass of deionized water is 1:(2~9), the ratio of the total mass of nonionic water-soluble monomers, anionic water-soluble monomers, hydrophobic monomers, amino nanocellulose, and deionized water to the mass of surfactant is 1:(0.001~0.02), the mass ratio of amino nanocellulose and cerium-containing compounds is 1:(0.1~1), and the mass ratio of cerium-containing compounds and complexing agents is 1:(0.1~1).
[0016] According to the present invention, preferably, in step (1), the mass ratio of nanocellulose, oxidant, and deionized water is 1: (0.1-3): (30-100);
[0017] Preferably, the oxidant is one of potassium periodate, sodium periodate and sodium metaperiodate;
[0018] According to the present invention, preferably, in step (2), the mass ratio of the aldehyded nanocellulose, the polyamine compound, the reducing agent, and the deionized water is 1: (0.5-5): (0.1-2): (50-200);
[0019] Preferably, the polyamine compound is one of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexaethyleneheptamine, heptaethyleneoctamine, or a mixture of two or more thereof;
[0020] Preferably, the reducing agent is one of sodium borohydride and potassium borohydride.
[0021] According to the present invention, preferably, in step (3), the mass ratio of the nonionic water-soluble monomer, the anionic water-soluble monomer, the hydrophobic monomer, and the amino nanocellulose is 1: (0.2-2): (0.01-0.2): (0.01-0.1);
[0022] Preferably, the ratio of the total mass of the nonionic water-soluble monomer, the anionic water-soluble monomer, the hydrophobic monomer, and the amino-modified nanocellulose to the mass of the deionized water is 1:(2-9);
[0023] Preferably, the ratio of the total mass of the nonionic water-soluble monomer, the anionic water-soluble monomer, the hydrophobic monomer, the amino nanocellulose, and the deionized water to the mass of the surfactant is 1:(0.001-0.02);
[0024] Preferably, the mass ratio of the amino nanocellulose to the cerium-containing compound is 1:(0.1-1), and the mass ratio of the cerium-containing compound to the complexing agent is 1:(0.1-1);
[0025] Preferably, the nonionic water-soluble monomer is one or a mixture of two or more of acrylamide, vinyl pyrrolidone, vinyl caprolactam, methacrylamide, N-hydroxymethyl acrylamide, N-ethyl acrylamide, N,N-dimethyl acrylamide, N-isopropyl acrylamide, hydroxyethyl acrylate, and hydroxypropyl acrylate;
[0026] Preferably, the anionic water-soluble monomer is one or a mixture of two or more of acrylic acid, methacrylic acid, maleic acid, itaconic acid, 2-acrylamido-2-methylpropanesulfonic acid, sodium vinyl sulfonate, sodium styrene sulfonate, and sodium allyl sulfonate;
[0027] Preferably, the hydrophobic monomer is one of dodecyl acrylate, hexadecyl acrylate, octadecyl acrylate, allyl dimethyl dodecyl ammonium chloride, allyl dimethyl hexadecyl ammonium chloride, allyl dimethyl octadecyl ammonium chloride, diallyl methyl dodecyl ammonium chloride, diallyl methyl hexadecyl ammonium chloride, and diallyl methyl octadecyl ammonium chloride, or a mixture of two or more thereof;
[0028] Preferably, the surfactant is one of OP-10, OP-15, OP-20, Tween 20, Tween 60, and Tween 80;
[0029] Preferably, the cerium-containing compound is one of ammonium cerium nitrate and ammonium cerium sulfate;
[0030] Preferably, the complexing agent is one of disodium ethylenediaminetetraacetate, trisodium ethylenediaminetetraacetate, pentasodium diethylenetriaminepentaacetate, and trisodium citrate;
[0031] Preferably, the pH is 5 to 8, the temperature is 0 to 10° C., and the reaction time is 3 to 6 hours.
[0032] The excellent effects of the present invention are as follows:
[0033] 1. The raw materials used in the present invention are easily available, the reaction conditions are mild, and the process is simple and safe.
[0034] 2. By modifying the nanocellulose by amino group, its dispersibility and reactivity in aqueous solution are improved, which is beneficial to the grafting of polymer segments on its surface; in addition, during the use of the water control agent, the cationization of the amino group is beneficial to enhance its adsorption and retention capacity in the formation.
[0035] 3. The polymer constructed with amino-modified nanocellulose as the core has branching characteristics and good molecular rigidity, and can still exhibit good long-term stability under high temperature and high salt conditions.
[0036] 4. In terms of three-dimensional structure, the water control agent is a "rod-shaped", "flexible shell-rigid core" structure. In the large pores, the water control agents form aggregates to form partial blockage, which is beneficial to improving the water control and erosion resistance effects.
[0037] 5. The post-processing process of the product of the present invention is simple and easy to realize continuous production.
[0038] 6. The product prepared by the present invention is easy to store and meets environmental protection requirements. DETAILED DESCRIPTION
[0039] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0040] The nanocellulose used in the following examples was purchased from Tianjin Wood Elf Biotechnology Co., Ltd., and the remaining materials, reagents, etc., unless otherwise specified, can be obtained from commercial sources.
[0041] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0042] Embodiment 1:
[0043] (1) Preparation of aldehyde-modified nanocellulose
[0044] 2 g of nanocellulose with a diameter of 5 to 10 nm and a length of 50 to 100 nm was added to 150 g of deionized water, and ultrasonic dispersion was performed. 2.5 g of sodium periodate was added, and the pH was controlled to 7, the temperature was controlled to 35° C., and the reaction was carried out in the dark for 5 h. The product was filtered, washed, and dried to obtain aldehyde-modified nanocellulose.
[0045] (2) Preparation of amino-modified nanocellulose
[0046] 1 g of aldehyded nanocellulose was added to 100 g of deionized water, and ultrasonic dispersion was performed. 3 g of diethylenetriamine was added, and the pH was controlled to 6, the temperature was controlled to 30°C, and the reaction was performed for 4 hours. After the reaction was completed, 1 g of sodium borohydride was added, the temperature was controlled to 25°C, and the reaction was performed for 3 hours. The product was filtered and dried to obtain amino nanocellulose.
[0047] (3) Preparation of branched polymers
[0048] 10 g acrylamide, 5 g acrylic acid, 0.1 g dodecyl acrylate, 0.1 g amino nanocellulose, 0.05 g Tween 80 and 90 g deionized water were added to a three-necked glass bottle equipped with a stirrer, a nitrogen tube and a thermometer. After stirring until all the raw materials were dissolved, nitrogen was introduced for 30 min, the pH was controlled at 6, the temperature was controlled at 0°C, 0.03 g disodium ethylenediaminetetraacetate and 0.05 g ammonium cerium nitrate were added, and the reaction was carried out for 3 h. The product was dried and crushed to obtain a branched polymer.
[0049] Embodiment 2:
[0050] As described in Example 1, except that the amount of nanocellulose added in step (1) is 3 g.
[0051] Embodiment 3:
[0052] As described in Example 1, except that the oxidant in step (1) is 3 g potassium periodate.
[0053] Embodiment 4:
[0054] As described in Example 1, except that the amount of diethylenetriamine added in step (2) is 2 g.
[0055] Embodiment 5:
[0056] As described in Example 1, except that the polyamine compound in step (2) is 4 g of tetraethylenepentamine.
[0057] Embodiment 6:
[0058] As described in Example 1, except that the reducing agent in step (2) is 1.5 g potassium borohydride.
[0059] Embodiment 7:
[0060] As described in Example 1, except that the amount of acrylamide added in step (3) is 8 g.
[0061] Embodiment 8:
[0062] As described in Example 1, the difference is that the non-ionic water-soluble monomer in step (3) is vinyl pyrrolidone.
[0063] Embodiment 9:
[0064] As described in Example 1, except that the amount of acrylic acid added in step (3) is 3 g.
[0065] Embodiment 10:
[0066] As described in Example 1, the difference is that the anionic water-soluble monomer in step (3) is methacrylic acid.
[0067] Embodiment 11:
[0068] As described in Example 1, except that the amount of dodecyl acrylate added in step (3) is 0.2 g.
[0069] Embodiment 12:
[0070] As described in Example 1, except that the hydrophobic monomer in step (3) is allyl dimethyl hexadecyl ammonium chloride.
[0071] Embodiment 13:
[0072] As described in Example 1, except that the surfactant in step (3) is 0.08 g OP-10.
[0073] Embodiment 14:
[0074] As described in Example 1, the difference is that the cerium-containing compound in step (3) is 0.03 g of ammonium cerium sulfate.
[0075] Embodiment 15:
[0076] As described in Example 1, except that in step (3), the complexing agent is 0.05 g of pentasodium diethylenetriamine pentaacetate.
[0077] Embodiment 16:
[0078] As described in Example 1, except that in step (3), the pH is 7, the temperature is 5° C., and the reaction time is 4 h.
[0079] Performance Evaluation
[0080] (1) Sample configuration
[0081] Simulated formation water was prepared according to the composition in Table 1. The products in Examples 1 to 16 were added to mineralized water at a concentration of 2500 mg / L and fully dissolved for later use.
[0082] (2) Water control performance test
[0083] The prepared polymer solution was subjected to displacement experiments and the water phase residual resistance coefficient, oil phase residual resistance coefficient and water-oil resistance ratio (NFRR) were calculated to evaluate the water control effect. During the experiment, the system temperature was maintained at 90 °C.
[0084] The permeability is calculated using Darcy's law.
[0085]
[0086] Where, K—permeability, mD;
[0087] μ—media viscosity, mpa·s;
[0088] L—sand filling pipe length, cm;
[0089] Q—permeable sand filling pipe flow rate, mL·s -1 ;
[0090] A—Cross-sectional area of sand filling pipe, cm 2 ;
[0091] ΔP—pressure difference before and after the sand filling tube experiment, MPa.
[0092] The residual resistance coefficient (RRF) is usually used to evaluate the reduction in permeability of the oil phase and the water phase after the water control agent treatment. w ) and oil phase residual resistance coefficient (RRF o )See Equation 2 and Equation 3.
[0093]
[0094] In the formula, K b,o —Oil phase endpoint permeability before water control agent treatment;
[0095] K a,o —Oil phase endpoint permeability after water control agent treatment;
[0096] K b,w —End point permeability of water phase before water control agent treatment;
[0097] K a,w —Permeability of water phase endpoint after water control agent treatment;
[0098] ΔP b,w —Pressure difference before water phase is injected into water control agent, MPa;
[0099] ΔP a,w —Pressure difference after water phase is injected with water control agent, MPa;
[0100] ΔP b,o —Pressure difference before oil phase is injected into water control agent, MPa;
[0101] ΔP a,o —Pressure difference after oil phase is injected with water control agent, MPa.
[0102] When NFRR(RRF w / RRF o ) is greater than 1, indicating that the permeability of the water phase after the water control agent treatment is reduced to a greater extent than the permeability of the oil phase, which means that the water control agent has a selective water control effect. After injecting 50 PV, the experimental results are shown in Table 2.
[0103] Table 1 Composition of simulated formation water
[0104]
[0105] Table 2 Residual resistance coefficient and water-oil resistance ratio of different samples
[0106] Sample No. <![CDATA[RRF w ]]> <![CDATA[RRF o ]]> NFRR Example 1 10.29 1.15 8.95 Example 2 9.92 1.18 8.41 Example 3 10.05 1.12 8.97 Example 4 10.34 1.16 8.91 Example 5 9.56 1.13 8.46
[0107] Table 2 Residual resistance coefficient and water-oil resistance ratio of different samples
[0108] Sample No. <![CDATA[RRF w ]]> <![CDATA[RRF o ]]> NFRR Example 6 10.46 1.24 8.44 Example 7 11.52 1.19 9.68 Example 8 8.45 1.16 7.28 Example 9 12.67 1.22 10.39 Example 10 12.38 1.17 10.58 Embodiment 11 13.04 1.14 11.44 Example 12 11.89 1.23 9.67 Example 13 14.35 1.16 12.37 Embodiment 14 10.56 1.21 8.73 Embodiment 15 9.87 1.14 8.66 Example 16 9.76 1.20 8.13
[0109] As shown in Table 2, after water injection of 50PV, the residual resistance coefficient of the water phase of each sample is much greater than 1, which indicates that after the injection of polymer, the resistance of the water phase increases significantly and the permeability decreases significantly. The residual resistance coefficient of the oil phase of each sample is between 1.1 and 1.3, which indicates that after the injection of water control agent, the permeability of the oil phase has no significant effect. In addition, the NFRR value of each sample is much greater than 1, and the highest value can reach 12.37, which indicates that each sample has excellent selective water control ability.
Claims
1. A branched polymer for selective water control in oil wells and a preparation method thereof, comprising the following steps: (1) Preparation of aldehyde-modified nanocellulose Add nanocellulose to deionized water, perform ultrasonic dispersion, add oxidant, control pH to 5-8, control temperature to 30-60°C, react for 2-6 hours in dark, filter, wash and dry the product to obtain nanocellulose; the diameter of nanocellulose is 4-10 nm, the length is 20-200 nm, and the mass ratio of nanocellulose, oxidant and deionized water is 1:(0.1-3):(30-100); (2) Preparation of amino-modified nanocellulose The aldehyded nanocellulose is added to deionized water, ultrasonically dispersed, a polyamine compound is added, the pH is controlled at 5-7, the temperature is controlled at 20-35°C, the reaction is carried out for 4-8 hours, and after the reaction is completed, a reducing agent is added, the temperature is controlled at 20-30°C, the reaction is carried out for 3-5 hours, and the product is filtered and dried to obtain the product; the mass ratio of the aldehyded nanocellulose, the polyamine compound, the reducing agent, and the deionized water is 1: (0.5-5): (0.1-2): (50-200); (3) Preparation of branched polymers Add nonionic water-soluble monomer, anionic water-soluble monomer, hydrophobic monomer, amino nanocellulose, surfactant and deionized water into a three-necked glass bottle equipped with a stirrer, a nitrogen tube and a thermometer, stir until all the raw materials are dissolved, introduce nitrogen for 30 minutes, control the pH to 5-8, and the temperature to 0-10°C, add a complexing agent and a cerium-containing compound, react for 3-6 hours, dry and grind the product to obtain; the mass ratio of nonionic water-soluble monomer, anionic water-soluble monomer, hydrophobic monomer and amino nanocellulose is 1:(0.2-2):(0.01 ~0.2):(0.01~0.1), the ratio of the total mass of nonionic water-soluble monomers, anionic water-soluble monomers, hydrophobic monomers, and amino nanocellulose to the mass of deionized water is 1:(2~9), the ratio of the total mass of nonionic water-soluble monomers, anionic water-soluble monomers, hydrophobic monomers, amino nanocellulose, and deionized water to the mass of surfactant is 1:(0.001~0.02), the mass ratio of amino nanocellulose and cerium-containing compounds is 1:(0.1~1), and the mass ratio of cerium-containing compounds and complexing agents is 1:(0.1~1). The oxidant is one of potassium periodate, sodium periodate and sodium metaperiodate; The polyamine compound is one of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexaethyleneheptamine, and heptaethyleneoctamine, or a mixture of two or more thereof; The reducing agent is one of sodium borohydride and potassium borohydride; The nonionic water-soluble monomer is one or a mixture of two or more of acrylamide, vinyl pyrrolidone, vinyl caprolactam, methacrylamide, N-hydroxymethyl acrylamide, N-ethyl acrylamide, N,N-dimethyl acrylamide, N-isopropyl acrylamide, hydroxyethyl acrylate, and hydroxypropyl acrylate; The anionic water-soluble monomer is one or a mixture of two or more of acrylic acid, methacrylic acid, maleic acid, itaconic acid, 2-acrylamido-2-methylpropane sulfonic acid, sodium vinyl sulfonate, sodium styrene sulfonate, and sodium allyl sulfonate; The hydrophobic monomer is one of dodecyl acrylate, hexadecyl acrylate, octadecyl acrylate, allyl dimethyl dodecyl ammonium chloride, allyl dimethyl hexadecyl ammonium chloride, allyl dimethyl octadecyl ammonium chloride, diallyl methyl dodecyl ammonium chloride, diallyl methyl hexadecyl ammonium chloride, and diallyl methyl octadecyl ammonium chloride, or a mixture of two or more thereof; The surfactant is one of OP-10, OP-15, OP-20, Tween 20, Tween 60 and Tween 80; The cerium-containing compound is one of ammonium cerium nitrate and ammonium cerium sulfate; The complexing agent is one of disodium ethylenediaminetetraacetate, trisodium ethylenediaminetetraacetate, pentasodium diethylenetriaminepentaacetate and trisodium citrate.
2. The branched polymer for selective water control in oil wells and the preparation method thereof according to claim 1, characterized in that: In step (1), the mass ratio of nanocellulose, oxidant and deionized water is 1:(0.1-3):(30-100).
3. The branched polymer for selective water control in oil wells and the preparation method thereof according to claim 1, characterized in that: In step (2), the mass ratio of the aldehyde-modified nanocellulose, the polyamine compound, the reducing agent and the deionized water is 1: (0.5-5): (0.1-2): (50-200).
4. The branched polymer for selective water control in oil wells and the preparation method thereof according to claim 1, characterized in that: In step (3), the mass ratio of the nonionic water-soluble monomer, the anionic water-soluble monomer, the hydrophobic monomer, and the amino-modified nanocellulose is 1: (0.2-2): (0.01-0.2): (0.01-0.1).
5. The branched polymer for selective water control in oil wells and the preparation method thereof according to claim 1, characterized in that: In step (3), the ratio of the total mass of the nonionic water-soluble monomer, the anionic water-soluble monomer, the hydrophobic monomer, and the amino-modified nanocellulose to the mass of deionized water is 1:(2-9).
6. The branched polymer for selective water control in oil wells and the preparation method thereof according to claim 1, characterized in that: In step (3), the ratio of the total mass of the nonionic water-soluble monomer, the anionic water-soluble monomer, the hydrophobic monomer, the amino nanofibers, and the deionized water to the mass of the surfactant is 1:(0.001-0.02).
7. The branched polymer for selective water control in oil wells and the preparation method thereof according to claim 1, characterized in that: In step (3), the mass ratio of the aminated nanocellulose to the cerium-containing compound is 1:(0.1-1), and the mass ratio of the cerium-containing compound to the complexing agent is 1:(0.1-1).
8. The branched polymer for selective water control in oil wells and the preparation method thereof according to claim 1, characterized in that: In step (3), the pH is 5 to 8, the temperature is 0 to 10° C., and the reaction time is 3 to 6 hours.
Citation Information
Cited By
Minoxidil mixed liquor and preparation method thereof
CN120478273A